2023
DOI: 10.1063/5.0125280
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and simulation on the micro-hollow cathode sustained discharge in helium with different geometries of the second anode

Abstract: The micro-discharge with a hollow cathode and a second anode with different geometries is experimentally and numerically studied. Effects of the second anode on the micro-hollow cathode sustained discharge (MCSD) in helium are investigated. Three kinds of electrodes with different geometries are used as the second anode. The results show that when needles are inserted into the plate to be used as the second anode, the formation of MCSD can be promoted, and MCSD can be obtained at a low cathode current. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The MCSD breakdown voltage is much lower in our case, likely because the pressure differential may extract charged particles from the MHCD electric field and pre-ionizes the gap between the MHCD and the substrate. In 2023, He et al [31] reported a similar regime in experiment using a third electrode covered with several needles. A relatively low voltage applied on the third electrode (200 V) is necessary to induce the breakdown.…”
Section: Mcsd Configurationmentioning
confidence: 82%
“…The MCSD breakdown voltage is much lower in our case, likely because the pressure differential may extract charged particles from the MHCD electric field and pre-ionizes the gap between the MHCD and the substrate. In 2023, He et al [31] reported a similar regime in experiment using a third electrode covered with several needles. A relatively low voltage applied on the third electrode (200 V) is necessary to induce the breakdown.…”
Section: Mcsd Configurationmentioning
confidence: 82%
“…However, it should be noted that fluid models [25][26][27][28][32][33][34][35] do not take into account nonlocal ionization by fast electrons in negative glow plasma in short glow discharges and discharges with a microhollow cathode. The main consequence of the nonlocality of the ionization source in the negative glow region is that the electric field strength in this region takes values close to zero, and the temperature of the main group of electrons is low and amounts to tenths of 1 eV [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Note that in recent years, hybrid models of gas-discharge plasma have gained great popularity, in which heavy particles (ions, excited particles, neutrals) are described by the fluid approximation equations, and electrons by the PIC/MCC method [34][35][36][37][44][45][46][47][48][49][50][51][52][53]. The idea of this method is as follows: the trajectory of an electron starting from the cathode is calculated according to the equations of motion mechanics in a given electric field; in this case, the elastic and inelastic scattering of an electron is taken into account as a random process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation